The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/17441692.2010.515235
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and HIV mitigation among people living with HIV in the era of anti-retroviral therapy: Emerging lessons from Côte d'Ivoire

Abstract: The effects of HIV/AIDS have been far-reaching in Africa. Beyond adverse health outcomes and the tremendous toll on life, AIDS has serious economic impacts on households, increasing livelihood insecurity while simultaneously depleting socio-economic resources. Although microfinance is believed to have the potential to mitigate the economic impacts of HIV by helping affected households and communities better prepare for and cope with HIV-related economic shocks, little empirical research exists on this subject.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…The results of the studies are promising; findings from a village savings and loan program, implemented by CARE International in Côte d'Ivoire, revealed that when appropriate medical treatment is available, PLHIV participate and benefit from microfinance activities, and enhance their economic self-sufficiency [71]. This qualitative study reported that by bringing individuals with similar experiences together, savings and loan groups also acted as self-support groups providing psychosocial support while reducing stigmatization and increasing members' sense of dignity and self-worth.…”
Section: Livelihood Interventions In the Context Of Hivmentioning
confidence: 86%
See 1 more Smart Citation
“…The results of the studies are promising; findings from a village savings and loan program, implemented by CARE International in Côte d'Ivoire, revealed that when appropriate medical treatment is available, PLHIV participate and benefit from microfinance activities, and enhance their economic self-sufficiency [71]. This qualitative study reported that by bringing individuals with similar experiences together, savings and loan groups also acted as self-support groups providing psychosocial support while reducing stigmatization and increasing members' sense of dignity and self-worth.…”
Section: Livelihood Interventions In the Context Of Hivmentioning
confidence: 86%
“…Research on how livelihood interventions need to be designed and implemented and their impact is just beginning to emerge [68,[71][72][73]. The results of the studies are promising; findings from a village savings and loan program, implemented by CARE International in Côte d'Ivoire, revealed that when appropriate medical treatment is available, PLHIV participate and benefit from microfinance activities, and enhance their economic self-sufficiency [71].…”
Section: Livelihood Interventions In the Context Of Hivmentioning
confidence: 99%
“…Analysis involved reading and rereading the data, identifying 30 inductive and deductive themes, and using descriptive analysis to describe the different dimensions and commonalities of each theme. Methods are described in greater detail in Holmes, Winskell, Hennink, and Chidiac (2011).…”
Section: Methodsmentioning
confidence: 99%
“…However, research has shown that targeting the multiple but interrelated needs of PLHIV can produce more sustainable results 3 5 . Limited evidence on the effect of community linkages demonstrates important associations between community support and improved clinical outcomes for PLHIV 6 8 . Further, Okello et al note that "… strengthening the capacity of community-based organizations to play a frontline role in implementing interventions in health, economic and social development is a prerequisite for transformational development.…”
Section: Introductionmentioning
confidence: 99%